Hubungan Pengetahuan dan Sikap Personal Hygiene dengan Kejadian Skabies di SD Negeri 2 Panggung Harjo Kecamatan Air Sugihan Kabupaten Ogan Komering Ilir Sumatera Selatan - Septi Ardianty (Jurnal Medika Cendikia, 2017)
Scabies is an infectious skin disease caused by Sarcoptes scabei. Scabies transmission can occur through direct contact with the scabies or contact with objects contaminated with scabies that may cause endemic scabies. If the scabies does not get treatment within a few weeks it will cause dermatitis caused by scratching. Scabies events worldwide are reported to be about 300 million cases per year and globally the scabies can affect more than 130 million people at any time with scabies events varying from 0.3% to 46%. The highest rates of scabies occur in tropical climates, high population density and low socioeconomic conditions in the Ogan Kemring Ilir area. Factors that affect the increased incidence of scabies is the lack of knowledge about personal hygiene, and bad attitudes can increase the infection of skin diseases of the scabies. Objective to know the correlation between knowledge and personal hygiene attitude with the occurrence of scabies At SD Negeri 2 Harjo Stage Air Sugihan Subdistrict of Ogan Komering Ilir Regency, the research was conducted in January until April 2017. This research used analytic observational design with cross- sectional. The number of samples is 60 respondents. The data obtained were analyzed by chi square statistic test. Univariate analysis result obtained respondents whose personal hygienical knowledge is not good as many as 36 (60%) respondents and bad attitude as much as 44 (68%). And respondents who experienced scabies that is as much as 33 (55%) of respondents. The result of chi square test of the relationship between personal hygiene knowledge and the occurrence of scabies got p value = 0,003 and correlation of attitude of hygiene personnel with scabies occurrence got P value = 0.001. Conclusion: There is a significant relationship of knowledge and personal hygiene attitude with the incident of scabies at SD Negeri 2 Panggung Harjo Air Sugihan Subdistrict Ogan Komering Ilir District South Sumatera.